2023
DOI: 10.7717/peerj.15319
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and metabolomic analysis of autumn leaf color change in Fraxinus angustifolia

Abstract: Fraxinus angustifolia is a type of street tree and shade tree with ornamental value. It has a beautiful shape and yellow or reddish purple autumn leaves, but its leaf color formation mechanism and molecular regulation network need to be studied. In this study, we integrated the metabolomes and transcriptomes of stage 1 (green leaf) and stage 2 (red-purple leaf) leaves at two different developmental stages to screen differential candidate genes and metabolites related to leaf color variation. The results of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Twenty-six metabolites, including anthocyanins, proanthocyanidins, and flavonoids, were simultaneously detected and quantified in different colored leaf species of A. mandshuricum [14]. Recently, 118 compounds were identified in the red and purple leaves of F. angustifolia, and the high contents of flavonoids indicate that they may be the main substances causing leaf color changes [16]. In this study, 26 carotenoids, 51 anthocyanins, and 2 chlorophyll, including zeaxanthin, lutein, α-carotene, and β-carotene, were identified in the processes of O. fragrans 'Wucaigui' leaf color changes (Tables 1-3).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six metabolites, including anthocyanins, proanthocyanidins, and flavonoids, were simultaneously detected and quantified in different colored leaf species of A. mandshuricum [14]. Recently, 118 compounds were identified in the red and purple leaves of F. angustifolia, and the high contents of flavonoids indicate that they may be the main substances causing leaf color changes [16]. In this study, 26 carotenoids, 51 anthocyanins, and 2 chlorophyll, including zeaxanthin, lutein, α-carotene, and β-carotene, were identified in the processes of O. fragrans 'Wucaigui' leaf color changes (Tables 1-3).…”
Section: Discussionmentioning
confidence: 99%
“…However, young tree leaves with a red color in tropical regions are the result of physiological causes (Wang et al, 2023), such as scavenging reactive oxygen species and defense against photoinhibition. Researchers observed that differences in relative humidity and light availability are related to autumn phenological variation.…”
Section: Literaturementioning
confidence: 99%
“…(maple) [28]. Transcriptome analysis of green leaves and red-purple leaves from Fraxinus angustifolia showed that there were nine differentially expressed genes related to anthocyanins [29]. However, research on the change in leaf color has been limited, especially in succulent plants.…”
Section: Introductionmentioning
confidence: 99%